Nutrition and farming practices as modulators of quality in gilthead seabream (Sparus aurata) - Matos, Elisabete (2016)
Gilthead seabream is the most important farmed species in the Mediterranean, and knowledge on how common farming practices impact its quality is limited. As such, this Thesis aimed to evaluate how gilthead seabream flesh quality is affected by some of these practices. In Chapter 2, the influence of nutritional factors was evaluated, specifically the high replacement of traditional marine-derived ingredients, both fishmeal and fish oil, with vegetable sources. We have seen that the vegetable-based diets tested did not greatly impact seabream flesh quality, although some alterations were seen in the fatty acid profile of the muscle. However, and despite having caused no alterations in flesh texture, vegetable ingredients reduced the amount of sulphated glycosaminoglycans in the extracellular matrix, affected muscle pH and reduced the activity of proteolytic enzymes. Throughout this Thesis, we measured for the first time the activity of proteolytic enzymes in seabream muscle, and cathepsin B was found to play a pivotal role in post-mortem muscle degradation. In Chapter 3, we evaluated the effect of harvesting and slaughter stress on seabream quality, and contrary to what is seen in most farmed species, our results show that gilthead seabream muscle structure is highly resistant to changes caused by stressful events. Nonetheless, considering that welfare is an increasingly important quality criterion, the use of a zero-withdrawal anaesthetic as a rested harvest technique or even slaughter method could prove valuable to the industry. In Chapter 4, we used maslinic acid as a dietary supplement, to modulate the muscle’s energetic status pre-mortem. As a finishing strategy, maslinic acid failed to increase levels of glycogen and ATP in the muscle. However, supplementation resulted in higher muscle fibre diameter and lower cathepsin B activity, and maslinic acid is likely to be useful to promote growth in this species. In general our Thesis has generated new knowledge to a major challenge facing the aquaculture industry, which is to find a compromise between the trends towards intensive rearing and consumer demand for healthy, high quality seafood being ethically acceptable and having a low impact on the environment.